Boreal Rivers as Sources of Terpenoid Emissions - Hashmi, Wasi; Zhang‐Turpeinen, Huizhong; Kohl, Lukas; Kuningas, Anne; Palacin‐Lizarbe, Carlos; Zhu, Xudan; Kinnunen, Niko; Marushchak, Maija E.; Rinne, Janne; Ojala, Anne; Berninger, Frank; Pumpanen, Jukka (Wiley-Blackwell, 2025)
Streams and rivers are biogeochemical hotspots that contribute substantially to inland water CO2 emissions. However, their role as sources of biogenic volatile organic compounds (BVOCs) remains poorly understood. We quantified terpenoid emissions from two boreal rivers in peatland and upland mineral soil catchments in Finnish Lapland based on monthly observations over two growing seasons. Both rivers were significant sources of terpenoid emissions, with predicted mean annual emissions of monoterpenes and sesquiterpenes around 4.9 ± 2.8 and 1.2 ± 0.8 mg m−2 year−1, respectively. The emissions were comparable to those from the boreal forest floor and other ecosystems, and they varied seasonally. The emission composition of the clear water river exhibited unclear seasonal variability and a greater diversity of compounds, while emissions of α-pinene and p-cymene showed distinct temporal trends in the brown water river. Dissolved organic carbon concentrations, SUVA254, and air temperature were the main drivers of seasonal variation in emissions. Our study revealed that boreal lotic ecosystems are a significant source of terpenoid emissions, which should be considered in the estimations of global ecosystem BVOC emissions.
Keywords: BVOC; rivers; boreal zone; gas fluxes; emissions; VOC